Methodical approaches to recreational and tourist cycles - fundamentals of recreational and tourist nature management - K. Kilinska; V. Yavorska; M. Zayachuk; P. Sukhy (Kazimierz Wielki University, 2021)
The article analyzes the essence and significance of recreational and tourist activities as a component of recreational and tourist cycles. Thus, recreation and tourism can be considered as a separate large block of nature - recreational and tourist nature management (RTP), which allows not only each person to use a favorable resource base for recreation, but also leads to changes in this area and the formation, as a result, multilevel ecological situations. The authors argue that a scientifically sound system of recreational and tourist resources is being formed, which helps tourists and vacationers to be aware of the geographical location of certain objects of recreation and contemplation.